RNA sequencing reveals the circular RNA expression profiles of osteoarthritic synovium. Issue 10 (12th June 2019) - Xiang, Shuai; Li, Zeng; Bian, Yanyan; Weng, Xisheng
Abstract: The role of circular RNAs (circRNAs) in regulating cartilage homeostasis in osteoarthritis (OA) has been reported. However, the regulatory mechanisms of circRNAs in OA synovium remains basically unidentified. The current study intended to divulge the expression profile of circRNAs in OA synovium and investigate the possible molecular mechanisms of circRNAs in synovitis in OA through an integrated bioinformatics analysis. A total of 35 synovium samples were collected, including 17 from patients with knee OA and 18 from controls. circRNA sequencing was then carried out on five OA synovium samples as well as five controls to explore the expression pattern of the circRNAs. Real‐time quantitative reverse transcription‐polymerase chain reaction (qRT‐PCR) was done to confirm the manifestation levels of six differentially expressed circRNAs. Gene Ontology (GO) as well as Kyoto Encyclopedia of Genes and Genomes pathway (KEGG) enrichment analyses were done for differentially expressed circRNAs using the DAVID database to annotate the functions. The circRNA‐miRNA coexpression network was then created to estimate the probable molecular regulatory mechanisms of specifically expressed circRNAs in OA synovium. Total of 122 circRNAs were found to be differentially expressed in OA synovium through RNA sequencing. The expressions of five downregulated circRNAs as well as an upregulated circRNA were confirmed through the use of qRT‐PCR. The circRNA‐miRNA network was created to annotate the probable molecular regulatory mechanisms of specifically expressed circRNAs. Our outcomes revealed that circRNAs might be incorporated in the initiation as well as development of OA synovitis and might have prospective importance in OA diagnosis and therapy. Abstract : Total of 122 circular RNAs (circRNAs) were detected to be differentially expressed in osteoarthritis (OA) synovium by RNA sequencing. The expressions of five downregulated circRNAs and an upregulated circRNA were confirmed by real‐time quantitative reverse transcription‐polymerase chain reaction (qRT‐PCR). The circRNA‐miRNA network was constructed to annotate the potential molecular regulatory mechanisms of specifically expressed circRNAs.